Maintaining Places of Social Inclusion: Ebola and the Emergency Department. (March 2021) - Wright, April L.; Meyer, Alan D.; Reay, Trish; Staggs, Jonathan
We introduce the concept of places of social inclusion—institutions endowed by a society or a community with material resources, meaning, and values at geographic sites where citizens can access services for specific needs—as taken-for-granted, essential, and inherently precarious. Based on our study of an emergency department that was disrupted by the threat of the Ebola virus in 2014, we develop a process model to explain how a place of social inclusion can be maintained by custodians. We show how these custodians—in our fieldsite, doctors and nurses—experience and engage in institutional work to manage different levels of tension between the value of inclusion and the reality of finite resources, as well as tension between inclusion and the desire for safety. We also demonstrate how the interplay of custodians' emotions is integral to maintaining the place of social inclusion. The primary contribution of our study is to shine light on places of social inclusion as important institutions in democratic society. We also reveal the theoretical and practical importance of places as institutions, deepen understanding of custodians and custodianship as a form of institutional work, and offer new insight into the dynamic processes that connect emotions and institutional work.